Gall stone ileus in the absence of gall bladder: a case report - Beniwal, Meenu; Singh, Vikram; ., Poonam; Singh, Paritev (International Surgery Journal, 2019)
Post cholecystectomy gall stone ileus is very rare with only few cases reported in the literature. This condition poses diagnostic challenges both because of its rarity and since the gall bladder had been removed previously. A high index of suspicion is needed for the diagnosis. Here, we report the case of a young female presented to the emergency room with acute intestinal obstruction. Patient underwent cholecystectomy followed by LSCS 20 yrs back. Patient was managed with explorative laparotomy which revealed an adherent, fibrosed and narrow segment of ileum containing a small impacted gall stone 120 cm from ileocaecal junction. Following the Resection anastomosis the patient made a satisfactory recovery and was discharged without any complication and is doing well.